PENGHAYATAN EKARISTI UMAT PAROKI SANTO YOHANES RASUL SOMOHITAN MENURUT KEVIN W. IRWIN - Roselawanto, Marcellinus (Jurnal Orientasi Baru, 2016)
The faithful of the Archdiocese of Semarang put a high respect on the Eucharist in their daily life. In many parishes, there are so many people who celebrate and participate in the Eucharist. Besides, they also try to understand and fully experience the Eucharist in their daily life among others. This research, concludes that the Eucharist as the expression of the faith was fully experienced by the people of Santo Yohanes Rasul Somohitan Parish. It was supported by many kinds of means and by the proper understanding of the Eucharist. The Eucharist also gave the positive influences to the personal growth and the sensitivity of the social situations. This research showed that there was a close relationship between lex orandi, lex credendi, and lex vivendi. What the people pray, is what people believe in, and what the people believe in, is what the people fully experience. The Eucharist’s full and comprehension in Santo Yohanes Rasul Somohitan parish should be evaluated continuesly. Based on that discovery, the Church was expected to give cathecism and other activities which could improve the Eucharist’s full and comprehension. And could give more positive influences to the community life.